O usuário e os sistemas de informatização: a utilização do sistema de controle de operações da Delegacia Legal pelos policiais civis do Estado do Rio De Janeiro - Carvalho Neto, Pedro Alcantara de (2008)
Organizing the information rationally and to systematize them has been essential for the success of several companies. When we study the institutions destined to the public security we realize that the use of technology and information systems are common in the examples prosperity of combat to the criminal practices. The Program Legal Police Station, inaugurated in Rio de Janeiro in 1999, follow that tendency, having one of their pillars in the care of the information treatment. The policemen that make registrations of the occurrences in the police stations using the Information System (SCO) have a fundamental role because through those registrations infractions are investigated , as well as a more complete database is fed to be allied in the elaboration of statistics and in the application of strategic actions. Considering that this kind of registration, using Information systems, modifies the institutional routine, the present study verifies if exist or not resistance to the use of the System - SCO, making an approach on the Information system, on the Program Legal Police Station, on the organizational culture and on the policemen’s opinion.